Testicular Parameters and its Influence in Buffaloes (Bubalus buballis) Sexual Behaviour - Hyppolito, Mariana; Zorzetto, Mariana Furtado; da Silva-Junior, Edjalma Rodrigues; Tironi, Stella Maris Teobaldo; Souza, Alessandra Gomes; Codognoto, Viviane Maria; Vieira, Andressa Filaz; Salgado, Leticia Cristina; Silva Marques, Nayara Fernanda; Oba, Eunice (Acta Scientiae Veterinariae, 2019)
Background: Brazil is one of the greatest bovine meat exporter in the world. However, the technologies applied at buffalo’s reproduction is not specific for this specie, adapted technics were established from the cattle breed. When the animal shows weight gain, gonadal and behavioral physiology fallow this tendency and the reproductive status become good and satisfactory. Thus, the aim of this study was to compare the reproduction characteristics of male buffaloes and its testicular parameters with sexual behavior. Materials, Methods & Results: Seven males Murrah breed with 67.29 ± 11.4 months of age were maintained at confinement for artificial shading. The testicular parameter was performed in restraint trunk and the sexual behavior evaluation was done with an estrus female. The sexual behavior was performed with an estrous female as a dummy. The testicular biometry was measured at the beginning and at the end of the experimental design, with the follow parameters: length, width, depth/thickness, scrotal circumference and the total volume. The data were submitted to the analysis of variance, and the means was compared with the Student-Newman-Keuls test, with significance difference P < 0.05 between the medians. The differences in the parameters were scrotal circumference (23.36 cm vs 24.86 cm), testicular length (8.71 cm vs 9.77 cm), right testicular width (8.57 cm vs 9.53 cm) and testicular volume (1.627.40 cm3 vs 2.149,68 cm3), respectively. The sexual behavior showed an increase in the Flehmen reflex, mounts (service capacity) and libido (2.00 vs 11.71; 0.57 vs 5.43; regular behavior vs very good behavior, respectively). Discussion: An increase in the testicular circumference was observed at the end of the experimental period with the values between 23.36 cm vs 24.86 cm. However, even with this increase of the testicular parameters it is lower than other male buffaloes with 36 months age. In Brazilian conditions, the testicular circumference variation is between 24.5 cm and 34 cm in animals with 60 months of age. These data shows that there are variations of the testicular parameters due to different systems of buffaloes breeding. When compared to cattle, buffaloes shows lower input of reproductive biotechnology. At the same way, the testicular growth and development depends of the nutrition and management used at the farm. In an inefficient system, buffaloes and bovine breeding could lose weight, testicular mass, and reduce testicular parameters. Besides that, the buffaloes can perform an improvement of a general condition when improvement of nutrition care occurs. The testicular parameters presents high correlation with the corporal and testicular development, which can be correlate to age and weight. Those parameters could help with the reproductive ability of the buffalo. The sexual behavior was increased and observed in the Flehmen reflex, service capacity and libido after the animal’s adaptation to the reproductive management. The buffaloes are animals extremely adaptable to different conditions, but need a period to adapt. Previous sexual experience is important during the social organization of the harem and helps in the practice of the sexual act. In these experimental conditions, we conclude that is necessary a social and behavior adaptation to the buffalo bull to present a better value of sexual characteristics to improve the fertility and production of Murrah buffaloes.